1981
DOI: 10.1029/gl008i001p00039
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and static moduli

Abstract: Static and dynamic bulk moduli (Ks and Kd) are measured as continuous functions of pressure from zero to 2‐3 kilobars for two sandstones, a tuff, limestone, granite, and oil shale. Results for the sandstones and granite are in good agreement with previously reported data with Ks/Kd varying from about 0.5 at atmospheric pressure to close to unity at pressures 2 kilobars and above. For rocks behaving elastically under static loading, the Ks/Kd ratio is inversely related to the microcrack density. For the limesto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
83
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(92 citation statements)
references
References 8 publications
9
83
0
Order By: Relevance
“…5.28, 5.29, and 5.30 show the ratio of static and dynamic Young's, bulk, and shear moduli, respectively, as functions of applied compressive stress. All these ratios presented similar trends: the higher the compressive stress, the higher the ratio, as we seen in the sandstones and granites studied by Cheng and Johnston (1981). In the first cycle, for compressive stresses lower than 30 bars during loading, the ratios were higher than for higher compressive stresses and unloading.…”
Section: Static and Dynamic Elastic Constants Comparisonsupporting
confidence: 63%
See 1 more Smart Citation
“…5.28, 5.29, and 5.30 show the ratio of static and dynamic Young's, bulk, and shear moduli, respectively, as functions of applied compressive stress. All these ratios presented similar trends: the higher the compressive stress, the higher the ratio, as we seen in the sandstones and granites studied by Cheng and Johnston (1981). In the first cycle, for compressive stresses lower than 30 bars during loading, the ratios were higher than for higher compressive stresses and unloading.…”
Section: Static and Dynamic Elastic Constants Comparisonsupporting
confidence: 63%
“…For example, Cheng and Johnston (1981) showed that the ratio between the static and dynamic bulk moduli, Ks/Kd, at atmospheric pressure is lower for samples with higher crack porosity:…”
Section: Static and Dynamic Elastic Constants Comparisonmentioning
confidence: 99%
“…Laboratory experiments [Cheng and Johnston, 1981;Adelinet et al, 2010] show that statically determined values of Young's modulus, E s , are always less than dynamically determined values, E d , and that the E s /E d ratio increases with confining pressure, and decreases with porosity and crack density. Here, confining pressure is estimated by integrating the product of the density and the depth (Figure 6d).…”
Section: Mechanical Properties Of the Crustmentioning
confidence: 99%
“…(d) Ambient lithostatic pressure computed from the presumed density structure. (e) Ratio of static to dynamic Young's modulus from laboratory measurements [Cheng and Johnston, 1981]. (f) Estimated static value of Young's modulus.…”
Section: Mechanical Properties Of the Crustmentioning
confidence: 99%
See 1 more Smart Citation